Molecular diversiry studies among blackgram genotypes for yellow mosaic virus resistance - V. Roja*, J. Sateesh Babu, N. Hari Satyanarayana, G. Bindumadhavi, P. Kishore Varma, N. Kamakshi, B. Jyothsna, J. Pranaya, K. Sudhamani and M.V. Ramana (Electronic Journal of Plant Breeding)
Yellow mosaic disease (YMD), incited by a geminivirus. Mungbean Yellow Mosaic Virus (MYMV), is transmitted by whiteflies, poses a significant threat to various leguminous crops in India. This study focuses on identifying resistant sources and validating molecular markers for their efficacy in detecting YMV resistance in blackgram. In the present study, 150 blackgram genotypes were evaluated to identify resistant sources for YMD under natural field conditions and through molecular markers. Among the 150 genotypes, 22 (both resistant and susceptible) were selected based on field screening. These genotypes were validated using 15 molecular markers, including 8 simple sequence repeats (SSRs) and 7 gene-specific markers linked to MYMV resistance. The markers amplified a total of 48 alleles, with polymorphic information content (PIC) values ranging from 0.82 (CEDG67) to 0.21 (HSP), with an average value of 0.55. The highest PIC values were exhibited by markers CEDG67 (0.82), CEDG115 (0.81), and CEDG20 (0.74). Cluster analysis using DARWIN revealed that most phenotypically resistant genotypes grouped together, while susceptible genotypes formed separate clusters. The genotypes LBG 904, LBG 932, LBG 884, PU 1815, PU 1808, PU 1803, MASH 1008, MASH 114, VBN 10, and PU 31 exhibited resistance to YMV phenotypically. Among these, LBG 904, LBG 932, PU 1815, PU 31, and MASH 1008 produced a 162 bp resistant allele using the marker CEDG180. Similarly, the gene-specific marker DEF produced a 190 bp resistant allele in all the resistant genotypes, whereas the susceptible genotypes produced both 190 and 250 bp alleles. These identified genotypes can serve as valuable sources for MYMV resistance in blackgram breeding programs.